2015
DOI: 10.1371/journal.pone.0128817
|View full text |Cite
|
Sign up to set email alerts
|

What Difference Does Patient and Public Involvement Make and What Are Its Pathways to Impact? Qualitative Study of Patients and Researchers from a Cohort of Randomised Clinical Trials

Abstract: BackgroundPatient and public involvement (PPI) is advocated in clinical trials yet evidence on how to optimise its impact is limited. We explored researchers' and PPI contributors' accounts of the impact of PPI within trials and factors likely to influence its impact.MethodsSemi-structured qualitative interviews with researchers and PPI contributors accessed through a cohort of randomised clinical trials. Analysis of transcripts of audio-recorded interviews was informed by the principles of the constant compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
153
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(165 citation statements)
references
References 26 publications
(31 reference statements)
7
153
0
Order By: Relevance
“…This is consistent with the finding of a recent UK consensus study that the majority of public participants felt that PPI leads to research of greater quality and relevance – a view only shared by a minority of academics . In keeping with a qualitative study of PPI in clinical trials, none of the participants reported negative impacts of PPI on research, although some expressed uncertainty about the impact of their own involvement. In our study, this seemed to be in part because of a lack of individual feedback on impact within specific research projects.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This is consistent with the finding of a recent UK consensus study that the majority of public participants felt that PPI leads to research of greater quality and relevance – a view only shared by a minority of academics . In keeping with a qualitative study of PPI in clinical trials, none of the participants reported negative impacts of PPI on research, although some expressed uncertainty about the impact of their own involvement. In our study, this seemed to be in part because of a lack of individual feedback on impact within specific research projects.…”
Section: Discussionsupporting
confidence: 88%
“…Many different terms are used internationally to describe patients and members of the public involved in research, such as ‘lay representative’, ‘patient partner’ and ‘public adviser’. In this study, we adopt the term ‘PPI contributor’ to avoid implying either that the small number of individuals typically involved in research can represent the diversity of perspectives among patients and the public or that the role of PPI contributors can always be described as a partnership …”
Section: Introductionmentioning
confidence: 99%
“…Engaging patients or public in research prior to study implementation is therefore seen to address their concerns, enhance trust, and can improve informed consent, mutual learning, recruitment and retention of research participants [9]. Patient and public involvement (PPI) is increasingly being advocated in health research to prevent harm to participants, improve the relevance of information sheets and the quality of informed consent [10, 11]. Boulanger (2013) however argues that little attention has been given to community engagement or PPI in TB research and this paper contributes to this knowledge gap [12].…”
Section: Introductionmentioning
confidence: 99%
“…It also is advantageous as it reinforces the ongoing nature of health care and can be a very important aspect of identifying paths to impact from a study (Dudley et al, 2015). It also is advantageous as it reinforces the ongoing nature of health care and can be a very important aspect of identifying paths to impact from a study (Dudley et al, 2015).…”
mentioning
confidence: 99%